Caracterización morfométrica de la cuenca alta del río Sauce Grande, Buenos Aires, Argentina - Gaspari, Fernanda Julia (2012)
The upper watershed of the Sauce Grande River supplies water to the hydraulic complex of the dike named Las Piedras, being a precious environmental service for the city of Bahia Blanca. A System of Payment for Environmental Services, as a basic strategy for territorial management and local development must be based on the water supply generated by the watershed. Analysis of morphometric and functional characteristics of a watershed, using parameters of shape, relief, and drainage, is basic for a hydrologic modelization, in order to establish the movement and capture of rainwater. The aim of this work was to make a morphometric characterization of the Upper Watershed of the Sauce Grande River. The methodology was based on the establishment and analysis of morphometric parameters, using a Geographic Information System and spreadsheets, obtained from a digital terrain model and satellite imagines. The area of the watershed was of 1502.6 km2, the axial longitude of 41.6 km, wit an mean wide of 36.1 km. The shape factor of 0.87 indicates an elongated shape, and the Gravellius coefficient of 2.8 indicates an oblong rectangular shape. The river length is 58336 m, with a mean slope of 0.0048 m.m-1. The drainage density is 0.2 km.km-2, with a sinuosity coefficient of 1.42. The concentration time is 11.8 hs. The adimensional hypsometric curve corresponds to a watershed with a high level of development. All the parameters ease water flow quantification in the watershed.